Sp3–sp3 carbon–carbon bond formation using 2-alkylazoles and a bromoacrylate as the reaction partners. Issue 29 (15th July 2015) - Zhao, Liqin; Derridj, Fazia; Djebbar, Safia; Bruneau, Christian; Doucet, Henri
Graphical abstract: Abstract: A carbonate base was found to promote the formation of sp 3 –sp 3 carbon–carbon bonds of 2-alkylazoles with a bromoacrylate. The reaction tolerates various alkyl substituents and a variety of heteroarenes such as thiazoles, oxazoles or imidazoles.